2024
DOI: 10.1007/s10143-024-02296-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of biologically effective dose on tremor decrease after stereotactic radiosurgical thalamotomy for essential tremor: a retrospective longitudinal analysis

Constantin Tuleasca,
Guillaume Carey,
Romain Barriol
et al.

Abstract: Stereotactic radiosurgery (SRS) is one of the surgical alternatives for drug-resistant essential tremor (ET). Here, we aimed at evaluating whether biologically effective dose (BEDGy2.47) is relevant for tremor improvement after stereotactic radiosurgical thalamotomy in a population of patients treated with one (unplugged) isocenter and a uniform dose of 130 Gy. This is a retrospective longitudinal single center study. Seventy-eight consecutive patients were clinically analyzed. Mean age was 69.1 years (median … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Other reported ailment include headaches, depression, minor cognitive deficits, sensory loss, and hemichoreiform movements ( 20 , 25 , 27 , 28 ). Tuleasca et al reported a correlation between BED and the severity of adverse effects ( 32 ). Permanent adverse effects were found in 15 patients including contralateral weakness, numbness, and speech disturbances.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other reported ailment include headaches, depression, minor cognitive deficits, sensory loss, and hemichoreiform movements ( 20 , 25 , 27 , 28 ). Tuleasca et al reported a correlation between BED and the severity of adverse effects ( 32 ). Permanent adverse effects were found in 15 patients including contralateral weakness, numbness, and speech disturbances.…”
Section: Resultsmentioning
confidence: 99%
“…Tuleasca et al made an assumption that the α/β ratio for normal brain is 2.47 Gy. In their study, it was shown that with BED between 4,300 and 4,500 Gy 2.47 , optimal response rates limiting ARE can be achieved ( 32 ).…”
Section: Discussionmentioning
confidence: 99%